The effectiveness of antibacterial treatment of the root canal in chronic apical periodontitis using an erbium-chromium laser - M. A. Postnikov; A. Yu. Rozenbaum; S. E. Chigarina; D. N. Kudryashov; M. B. Khaikin; I. V. Khramova; G. N. Belanov (Эндодонтия Today, 2022)
Aim. To evaluate the effectiveness of antibacterial treatment of root canals in chronic apical periodontitis with an erbiumchromium laser.Materials and methods. Group I consisted of 16 patients – antibacterial treatment of root canals was carried out with 10 ml of 3% solution of sodium hypochlorite «Belodez». Group II – 29 patients – antibacterial treatment was carried out with an erbium-chromium laser Waterlase MD in the following mode: wavelength – 2780 nm, power – 1.5 W, pulse duration – 140 μs, frequency – 40 Hz. Antibacterial efficacy was assessed by the results of microbiological studies of samples from the root canal before and after antibacterial treatment. Results. During antibacterial treatment with an erbium-chromium laser, a statistically significant decrease in the concentration of Escherichia coli, Staphylococcus aureus, Moraxella lacunata, Actinomyces israelii, Streptococcus mutans, Corynebacterium xerosis occurred in comparison with the control group.Conclusions. The dynamics of clinical signs in patients of the two groups indicates the anti-inflammatory effect of the Waterlase MD erbium-chromium laser, which confirms a pronounced antibacterial effect against Escherichia coli, Corynebacterium xerosis, Actinomyces israelii, Streptococcus mutans, Staphylococcus aureus, Moraxella lacunata.